EFFECTIVENESS OF DIGITAL FINANCIAL SERVICES IN ENHANCING FISHERY LOAN ACCESSIBILITY IN WEST BENGAL - Amrita Das Gupta,; Kazi Mainuddin,; Manisha Naskar, (The Bioscan, 2025)
The purpose of this study is to evaluate the effectiveness of digital financial services in enhancing fishery loan accessibility in West Bengal, India. A comprehensive literature review has been conducted to collect information from relevant books, journals, articles, reports, and government websites. However, this study has specifically focused on the “Matsyajeebi Credit Card (MJCC)” scheme, which is one of the current and active digital financial service systems applicable to fishery practices in West Bengal. This study has revealed that this digital banking or funding system in this state has helped to improve loan accessibility in the fishery industry. Many fishermen have benefited from such digital financial services, which further positively reflects the success and growth of the overall fishery sector.